Radiosurgery for Arteriovenous Malformations Using Micro–Multi-leaf Collimators: Analyses of Outcome - Anjanappa, Milan; Jayadevan, E. R.; Bhasi, Saju; Koshy, Sumod M.; George, Preethi S.; Arjunan, Asha; Raghukumar, P.; Mathew, Beela S. (Indian Journal of Neurosurgery, 2017)
Aim To assess the outcome of patients with AVMs treated using micro-MLC–based radiosurgery at Regional Cancer Centre (RCC), Thiruvananthapuram.Materials and Methods During January 1 to December 31, 2012, 24 patients were treated with stereotactic radiosurgery (SRS) at RCC. The median age was 28 years (range: 8–58 years). There were 11 males and 13 females. Fifteen patients had prior embolization. All patients were treated with a frameless radiosurgery system using micro-MLC–based linear accelerator (LINAC). Obliteration of the lesion was assessed with either magnetic resonance angiogram (MRA) or digital subtraction angiography (DSA).Results Nineteen patients who underwent an assessment procedure were evaluable for this study. At median follow-up of 12 months, nearly two-thirds of patients had complete obliteration of the AVM and the rest had partial obliteration. Among patients with complete obliteration, seven patients had an AVM volume of ≤ 3 cc and three-fourths of the patients had AVM score of < 1.5. Further, marginal dose of > 18 Gy resulted in higher obliteration. One patient had an episode of seizure after SRS. No complications or bleed was seen in any of the patients after treatment.Conclusion Our experience correlates with the existing literature reports, without any significant complications. Longer follow-up is required to assess the complete obliteration and late complications.
Keywords: venous malformation; stereotactic radiosurgery; LINAC; micro–multi-leaf collimators